Α-Terthienylmethanol, isolated from Eclipta prostrata, induces apoptosis by generating reactive oxygen species via NADPH oxidase in human endometrial cancer cells. (1st July 2015) - Lee, Jae-Seung; Ahn, Ji-Hye; Cho, Yoon-Jin; Kim, Ha-Yeong; Yang, Yeong-In; Lee, Kyung-Tae; Jang, Dae-Sik; Choi, Jung-Hye
Abstract: Ethnopharmacological relevance: Eclipta prostrate L. (syn. E. alba Hassk), commonly known as False Daisy, has been used in traditional medicine in Asia to treat a variety of diseases, including cancer. Although an anti-tumor effect has been suggested for E. prostrata, the exact anti-tumor effects and underlying molecular mechanisms of its bioactive compounds are poorly understood. The aim of this study was to identify compounds with anti-cancer activity from E. prostrata and to investigate their mechanism of action. Materials and methods: To assess cell viability, cell cycle progression, and apoptosis, we performed MTT assays and FACS analysis using Annexin and PI staining. We also investigated reactive oxygen species (ROS) production and caspase activation using flow cytometry and Western blot analysis, respectively. Cytosolic translocation of cytochrome c was measured using an ELISA kit. Antioxidants, MAPK signaling inhibitors, NADPH oxidase inhibitors, and siRNA were used to elucidate the molecular mechanism of action of the compound. Results: We isolated five terthiophenes from the n -hexane fraction of E. prostrata ; of these, α-terthienylmethanol possessed potent cytotoxic activity against human endometrial cancer cells (Hec1A and Ishikawa) (IC50 <1 μM). The growth inhibitory effect of α-terthienylmethanol was mediated by the induction of apoptosis, as shown by the accumulation of sub-G1 and apoptotic cells. In addition, α-terthienylmethanol triggered caspase activation and cytochrome c release into the cytosol in a time-dependent manner. Moreover, α-terthienylmethanol increased the intracellular level of ROS and decreased that of GSH, and the antioxidants N-acetyl-l -cysteine and catalase significantly attenuated α-terthienylmethanol-induced apoptosis. We further demonstrated that inhibition of the NADPH oxidase attenuated α-terthienylmethanol-induced cell death and ROS accumulation in endometrial cancer cells. Conclusion: Overall, these results suggest that α-terthienylmethanol, a naturally occurring terthiophene isolated from E. prostrata, induces apoptosis in human endometrial cancer cells by ROS production, partially via NADPH oxidase. Graphical abstract: